Parietal peritoneal closure versus non-closure at caesarean section: which technique is feasible to perform?. (July 2013) - Kiykac Altinbas, Sadiman; Cenksoy, Pinar; Tapisiz, Omer Lutfi; Beydilli, Gulay; Yirci, Bülent; Ercan, Önder; Dede, Suat; Kandemir, Omer
Abstract Objective: To evaluate short-term effects of closure versus non-closure of the parietal peritoneum at caesarean section. Methods: A randomized controlled study of women undergoing caesarean section was conducted at the obstetrics department of a research and education hospital between October 2010 and May 2011. Patients were randomly assigned to have closure of parietal peritoneal layer (Group I, n = 55), and non-closure of parietal peritoneal layer (Control, Group II, n = 55). Intra-operative and post-operative outcomes were compared between the groups. Results: Groups were similar for baseline characteristics. Although there was statistically significant difference between Group 1 and Group 2 in terms of time to oral intake and mobilization time [12 (8–12) versus 8 (8–10) h; p < 0.001; 12 (8–12) versus 8 (8–10) h; p < 0.001]; the other variables, such as drop in hemoglobin concentration, estimate of blood loss, intra-operative additional sutures, operating time and time to passage of flatus [1.13 ± 0.86 versus 1.41 ± 0.82 g/dL; 487.9 ± 217.01 versus 544.87 ± 237.64 mL; 0 (0–1) versus 0 (0–1); 30.8 ± 7.63 versus 31.6 ± 10.38 h; 18.2 ± 6.04 versus 18.2 ± 4.23 h, p > 0.05] were not statistically different between Group 1 and Group 2. Conclusions: Closure of the parietal peritoneum has no benefit over non-closure of parietal peritoneum and non-closure is associated with rapid post-operative recovery.